Teachers' strategies for stimulating fine motor skills in early childhood in coloring extracurricular activities at Muslimat NU 001 Ponorogo Kindergarten: Strategi Guru Dalam Menstimulasi Motorik Halus Anak Usia Dini Pada Kegiatan Ekstrakurikuler Mewarnai di TK Muslimat NU 001 Ponorogo - kafaina ittaqoina; Tirta Dimas Wahyu Negara (UIN Kiai Ageng Muhammad Besari, 2024)
Early childhood is a very important period to provide stimulation so that children's growth and development becomes optimal. Fine motor development is one aspect of development in children that must receive stimulation. Fine motor development is related to a child's ability to carry out activities involving small muscles that require coordination between the eyes, hands and brain as the control center. As a facilitator in the learning process the teacher must be able to choose the right strategy to achieve the learning objectives. Strategy is something that is prepared to achieve certain goals. This research uses a qualitative approach with a qualitative descriptive research type. Data collection techniques are observation, interviews and documentation. The data analysis technique uses the Miles and Huberman concept, namely through data reduction, data presentation, and drawing conclusions from research. The results of the research found that: 1) The fine motor skills of young children at TK Muslimat NU 001 Ponorogo have developed well. 2) Strategies used by teachers in training fine motor skills in early childhood at Muslimat NU 001 Ponorogo Kindergarten 1) Introduction of colors to children carried out by teachers; 2) Teach children good and correct coloring techniques; 3) Guide, give examples and provide explanations directly in front of the child.